Sulphur-isotope compositions of pig tissues from a controlled feeding study. Issue 1 (1st January 2017) - Webb, Emily C.; Newton, Jason; Lewis, Jamie; Stewart, Alan; Miller, Bevis; Tarlton, John F.; Evershed, Richard P.
ABSTRACT: Sulphur-isotope determinations are becoming increasingly useful for palaeodietary reconstruction, but knowledge of isotopic discrimination between diet and various tissues remains inadequate. In this study, we explore the sensitivity of δ 34 Stissue values to changes in δ 34 Sdiet values, sulphur isotopic discrimination between diet and consumer, and the potential impact of terrestrial vs. marine protein consumption on these discrimination offsets. We present new δ 34 S values of bone collagen, muscle, liver, hair, milk and faeces from ten mature sows, ten piglets and fifteen adolescent pigs from a controlled feeding study. The δ 34 Stissue values were found to co-vary with the δ 34 Sdiet values, the δ 34 Stissue – δ 34 Sdiet isotopic offsets (Δ 34 Stissue-diet ) are small but consistent, and dietary protein source does not systematically alter the Δ 34 Stissue-diet isotopic discrimination. The outcomes of this study are of particular relevance to questions that are difficult to resolve using carbon and nitrogen stable isotopes alone, and will also be useful in regions where terrestrial, freshwater, and marine resources could have all potentially contributed to human diet.